Acute complicated jejunum diverticulitis: a case report with a short literature review - Chiorescu, Stefan; Mocan, Mihaela; Santa, Maria Elena; Mihăileanu, Florin; Chiorescu, Roxana Mihaela (Frontiers in Medicine, 2024)
Introduction Jejunal diverticulosis is a rare condition. Most of the time, it is asymptomatic; but it can cause severe complications such as intestinal perforation, mechanical occlusion, and hemorrhage. Case presentation A patient aged 78 years, with a history of biological aortic valve prosthesis, atrial fibrillation, type 2 diabetes mellitus, and chronic obstructive pulmonary disease, presented in the emergency department for acute abdominal pain in the lower abdominal floor, nausea, and inappetence. Abdominal computed tomography revealed an inflammatory block in the hypogastrium, agglutinated small intestinal loops, fecal stasis, and air inclusions. Pulled mesentery and associated internal hernia are suspected. Exploratory laparotomy was performed, revealing an inflammatory block in the hypogastrium, whose dissection revealed inner purulent collection and the appearance of jejunal diverticulitis, a diagnosis confirmed by histopathological examination. Segmental resection of the jejunum with double-layer terminal–terminal enteroenteric anastomosis, lavage, and drainage was performed. The evolution was favorable. Conclusion Based on our brief review, the diagnosis of complicated jejunal diverticulosis is difficult and sometimes not accurately established, even by high-resolution imaging techniques, with diagnostic laparotomy being necessary for these situations. Surgical treatment should be considered before severe complications develop.